Molecular Research on Platelet Activity in Health and Disease - Savini, Isabella; Gasperi, Valeria; Catani, Maria Valeria (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The present book, which includes eleven articles five reviews and six original studies published in the Special Issue "Molecular Research On Platelet Activity in Health and Disease", gives an international picture of the up-to-date understanding of (i) platelet signaling under physiological and pathological conditions; (ii) novel technologies for monitoring platelet functions; and (iii) clinical applications of platelet-based-therapy for management of pathological conditions, not directly related to hemostasis and thrombosis. The book reveals novel aspects of platelet biology, and will be helpful for offering new insights and a research impetus for those who are interested in developing new therapeutic tools for the management of pathological conditions depending on platelet dysfunctions.